Unveiling the Impact Digital Marketing Strategies and Business Performance in the Beauty Industry - Hemachandra; Aditya Kusuma (Journal on Economics, Management and Business Technology, 2024)
This research delves into the profound impact of digital marketing strategies on business performance within the dynamic landscape of the beauty industry. Through a mixed-methods approach encompassing quantitative analysis of primary survey data and qualitative examination of interviews and focus groups, the study unravels the intricate relationship between marketing initiatives and key performance indicators. The findings underscore the transformative power of digital marketing investments in driving revenue growth and amplifying brand visibility for beauty brands. Moreover, the study illuminates the importance of authenticity, relevance, and personalization in digital marketing content and consumer engagement initiatives. Influencer collaborations, personalized marketing tactics, and community-building efforts emerge as potent tools for cultivating meaningful connections with consumers and fostering brand loyalty. Additionally, the research highlights the interconnectedness of digital marketing strategies across various channels and touchpoints, emphasizing the significance of omnichannel integration in delivering cohesive brand experiences. By embracing consumer-centric approaches and prioritizing innovation, beauty industry practitioners can navigate the complexities of the digital landscape and sustain growth in an increasingly competitive marketplace.